Ontogenetic shifts, habitat use and community structure: how fishes use and influence protected tallgrass prairie streams - Martin, Erika C. (Kansas State University, 2014)
This dissertation consists of three research-based chapters which focus on habitat association of prairie stream fishes and how these fish communities influence stream ecosystem properties. Chapter one introduces important concepts used throughout the chapters, and describes my study streams. In chapter two, I identify local habitat factors associated with the diversity and density of fishes in two protected prairie watersheds. Specifically, the relative importance of habitat factors associated with fish communities were evaluated along a stream-size gradient and across multiple seasons and years. I found that species richness was positively associated with pool area and discharge. Redundancy analyses showed common prairie fish species exhibit ontogenetic habitat associations, with adults in deep and juveniles in shallow pools. Chapter 3 addresses how fish species richness in small prairie streams affects whole-stream metabolism and biomass distribution of benthic organic matter, algal and macroinvertebrates. This study was conducted by stocking experimental stream mesocosms that included pool-riffle habitats with three different communities that represent a gradient of species richness of headwater prairie streams from one to three common prairie stream fish species. I illustrated how species influence ecosystems across multiple spatial scales and found that different communities altered the distribution of algal biomass from benthic surfaces to floating mats and from pools to riffles. The objective of the fourth chapter was to quantify how two size classes of herbivorous prairie stream fish species, central stoneroller Campostoma anamolum and southern redbelly dace Chrosomus erythrogaster differentially affect stream ecosystem properties. This study was also conducted in experimental stream mesocosms, where each unit consisted of one riffle and one pool. Using ANOVAs, I found large dace were associated with longer filaments (F = 7.5, P = 0.002, df = 4) and small fishes with less benthic organic matter (F = 4.2, P = 0.02, df = 4). There was no evidence for ontogenetic shifts in diet and likely differences in energetic requirements and behavior drove the differences among treatments. My research finds that small-bodied prairie stream fishes have predictable habitat preferences and effects on stream properties are dependent on species identity, richness and size structure.
Keywords: stream ecology; Fish ecology; Ontogenetic shift; Habitat associations; Ecology (0329)